2014
DOI: 10.3390/ijerph111010406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of a Novel Molluscicide in the Endemic Schistosomiasis Japonica Area of China

Abstract: Oncomelania hupensis is the sole intermediate host snail of Schistosoma japonicum in China. Snail control by molluscicide remains one of the most effective measures of schistosomiasis japonica control. A 50% wettable powder of niclosamide ethanolamine salt (WPN) is widely used for snail control in China. However, WPN is costly and toxic to fish. A novel molluscicide named LDS, the salt of quinoid-2′, 5-dichloro-4′-nitrosalicylanilide from niclosamide, has been developed. To evaluate the effects of large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…Hubei has been an endemic hotspot for schistosomiasis, which may be related to its lake and marshland regions [ 42 ] and other biological and social factors that facilitate the transmission of S. japonicum [ 43 ]. In the present study, we found that Hubei accounted for >50 % of all human S. japonicum infections in China during 2009–2014, which indicates that better control strategies and measures are needed in Hubei.…”
Section: Discussionmentioning
confidence: 99%
“…Hubei has been an endemic hotspot for schistosomiasis, which may be related to its lake and marshland regions [ 42 ] and other biological and social factors that facilitate the transmission of S. japonicum [ 43 ]. In the present study, we found that Hubei accounted for >50 % of all human S. japonicum infections in China during 2009–2014, which indicates that better control strategies and measures are needed in Hubei.…”
Section: Discussionmentioning
confidence: 99%
“…In China, some molluscicides have also been reported as effective and less toxic, such as the suspension concentrate of niclosamide [ 50 ]. A promising study was conducted by Xia et al [ 51 ] using a novel molluscicide derivative from niclosamide, named LDS (salt of quinoid-2′, 5-dichloro-4′-nitrosalicylanilide). To assess the effects of large-scale field applications of LDS, tests were done in 15 counties in the endemic S. japonica areas of Hubei province, China.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effects of large-scale field applications of LDS, tests were done in 15 counties in the endemic S. japonica areas of Hubei province, China. However, despite showing good results of mollusc mortality, these studies also need to clarify its impact on the environment [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Niclosamide was selected as a molluscicide in the 1950s after screening of well over 20,000 compounds for toxicity against the schistosome-transmitting snail Biomphalaria glabrata [ 7 ]. Currently, Bayluscide, containing niclosamide or its ethanolamine salt, is still being applied in many endemic areas, mostly in Africa and Asia [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%